PENGARUH NILAI PELANGGAN DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN KARTU HALO TELKOMSEL (STUDI PADA PELANGGAN KARTU HALO DI SEMARANG) - Martea Hayu Nuraeni, 15.05.61.0001; Sutejo, Bambang (Students' Journal of Economic and Management, 2019)
This study aims to analyze the influence of customer value and trust in customer satisfaction. This research was conducted at Grapari Telkomsel Semarang. The population in this study were TelkomHalo kartuHalo customers. The number of samples used in this study were 100 people. Data collection is done by questionnaire with purposive sampling technique. The data analysis technique used is multiple linear regression analysis to determine the effect of customer value variables and confidence in satisfaction of Telkomsel kartuHalo customers in Semarang. The results of the study show that (1) customer value has a positive and significant effect on customer satisfaction (2) trust does not have a positive and significant effect on customer satisfaction.